Chest ultrasound for the diagnosis of paediatric pulmonary diseases: a systematic review and meta-analysis of diagnostic test accuracy. Issue 1 (17th December 2018) - Heuvelings, Charlotte C; Bélard, Sabine; Familusi, Mary A; Spijker, Rene; Grobusch, Martin P; Zar, Heather J
Abstract: Background: Chest ultrasound is an emerging imaging modality, for several paediatric pulmonary diseases. Sources of data: MEDLINE and EMBASE (1946–47 to 10 March 2017) were searched to collect evidence on the diagnostic accuracy of chest ultrasound, compared to other imaging modalities, for the diagnosis of paediatric pulmonary diseases. Areas of agreement: Eighteen pneumonia studies, comprising 2031 children, were included for meta-analysis; the summary estimate sensitivity was 95.0% (95%CI: 90.7–97.3%) and specificity was 96.1% (95%CI: 89.1–98.7%). Areas of controversy: Other pulmonary diseases also yielded high sensitivity and specificity, but a meta-analysis could not be conducted due to a limited number of studies includable, and their heterogeneity. Growing points: Chest ultrasound should be considered as a first-line imaging modality for children with suspected pneumonia. Areas timely for developing research: Further research should focus on the diagnostic accuracy of chest ultrasound for the diagnosis of paediatric pulmonary diseases, other than pneumonia, comparing against a valid gold standard.